Meningkatkan Hasil Belajar PAKAT dengan Model PBL Fase D Kelas 9 SMPN 4 Tebing Tinggi - Fitri Maria Sinaga; Ansemus Joko Prayitno (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The low learning outcomes in Catholic religion for 9th-grade students are a problem, and the root of the problem is teachers' propensity to employ a traditional teaching style called lecturing. The researcher tries to apply the PBL approach to enhance learning results. Both qualitative and quantitative descriptive research models are used in this study. SMPN 4 Tebing Tinggi is the research site. The study's findings suggest that applying the PBL approach can enhance students' learning objectives. The fact that learning results improved from cycle 1 to cycle 2 with data showing that in the cognitive aspect, the competent category is at 22.2% and the proficient category at 77.8%. In the affective aspect, the competent category is at 11.1%, and the proficient category is at 88.9%. A similar trend is observed in the psychomotor aspect, with the competent category at 11.1% and the proficient category at 88.9%. The study concludes that the use of the PBL model in learning can enhance the learning outcomes of 9th-grade students.